31. PERCEPTION OF THE CLINICAL LEARNING ENVIRONMENT AMONG NURSING STUDENTS OF HANOI MEDICAL UNIVERSITY IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: (1) To survey the perception of clinical learning environment of nursing students at Hanoi Medical University; (2) To study some factors related to the perception of clinical learning environment of nursing students at Hanoi Medical University.Research method: Cross-sectional descriptive study using self-administered questionnaire Clinical Learning Environment Inventory Vietnamese version (V-CLEI).Results: The average score of V-CLEI scale is 133.2 ± 11.7, the lowest score is 102 points, the highest is 163 points. The year of study of nursing students is related to the perception of clinical learning environment, the higher the year of study, the higher the perception of nursing students about clinical learning environment.Conclusion: The perception of nursing students at Hanoi Medical University about the clinical learning environment reached 133.2 ± 11.7, students are aware of the work that a nursing staff must do, they strive to complete the assigned tasks, and are aware that clinical learning is extremely necessary and not a waste of time. However, there are stilllimitations: lack of creativity in the clinical learning environment, inappropriate division of work, and overload of work.
Keywords: Perception; clinical learning environment; nursing students; Hanoi Medical University